Containers and bags with family names sent for milling - Mumbai Archive Project Team (Jio Institute, 2024)
Stacks of containers and bags sent for milling are marked with family names for identification. Once the spices are fully powdered, they are kept at the mill to be collected in a day or two. Each family has a unique mix of spices, which must be pounded separately so that the flavours and aromas do not mix.